2018
DOI: 10.1002/alr.22146
|View full text |Cite
|
Sign up to set email alerts
|

Revision endoscopic sinus surgery rates by chronic rhinosinusitis subtype

Abstract: All CRS subtypes demonstrated clinically meaningful improvement in postoperative SNOT-22 scores following ESS. Our overall revision ESS rate was 4% (3.5% in CRSwNP). AFS, AERD, and EGPA groups demonstrated low revision rates, while immunodeficiency and GPA patients required more revision surgery. A contemporary understanding of CRSwNP subtypes facilitated surgical and medical strategies in improving outcomes for AERD, AFS, and EGPA patients. CRSsNP subtypes with immunodeficiency and GPA merit further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 20 publications
4
71
2
Order By: Relevance
“…Asthma and AERD have been previously associated with recalcitrant CRSwNP . Our study found that patients with recurrent CRSwNP were more likely to have AERD than patients with primary CRSwNP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Asthma and AERD have been previously associated with recalcitrant CRSwNP . Our study found that patients with recurrent CRSwNP were more likely to have AERD than patients with primary CRSwNP.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that CRSwNP negatively affects quality of life and is a common problem worldwide, with prevalence estimates of 0.2%‐4% . While surgery provides significant benefit in symptomatology and respiratory health, as many as 40% of the patients with CRSwNP may develop recurrent polyposis within 12 months postoperatively . Clinical factors such as asthma prevalence, as well as aspirin‐exacerbated respiratory disease (AERD), appear to be associated with higher recurrence rates of nasal polyps .…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rates of CRS have been reported in a large retrospective cohort study of 61,000 patients which found that the revision ESS rate is 6.65%. This same study used multivariable regression modeling to identify patients with CRSwNP as being at higher risk of having revision surgery [60]. The impact of S. aureus on the effectiveness of ESS has not been studied in detail, but variations in the nasal microbiome may impact the outcome of sinus surgery [61].…”
Section: Role Of Surgerymentioning
confidence: 99%
“…There are a number of patient‐specific factors that have been reported to impact disease course in CRSwNP. Patients with allergic fungal rhinosinusitis (AFRS) and aspirin‐exacerbated respiratory disease (AERD) phenotypes typically undergo revision surgery at higher rates . Younger age, comorbid asthma, allergy, and prior surgery have also been associated with increased revision rates …”
mentioning
confidence: 99%
“…Surgeon‐specific factors that may decrease revision rates include performance of septoplasty, endoscopic Lothrop surgery, complete ESS rather than targeted or focal surgery, and use of postoperative steroid rinses . There have been numerous single‐institution studies exploring revision rates in CRSwNP; however, these studies often examined patient‐ or surgeon‐specific factors in isolation . For example, despite increased use of postoperative steroid rinses in recent years, there have been few single‐institution studies that considered compliance with medical therapy along with extent of surgery when predicting surgical success rates .…”
mentioning
confidence: 99%